The Evaluation of Employee Tax Incentive during Covid-19 Pandemic: A Study on Commerce Industry in Jakarta - Hamzah, Umar; Tambunan, Maria R.U.D. (UI Scholars Hub, 2023)
The Covid-19 pandemic has had impacts on various aspects of human life, particularly economic activities. In response to this situation, the government issued an income tax incentive policy for employees borne by the government (PPh 21 DTP) to maintain the purchasing power of the community, especially for employees during the pandemic. Until the end of 2020, the realization report of this incentive utilization was still low, reaching only 29.8% of the budget ceiling. This study aims to evaluate the PPh 21 DTP tax incentive policy using Dunn's policy evaluation criteria (2004). Policy evaluation covers aspects of effectiveness, efficiency, sufficiency, fairness, responsiveness, and accuracy. This research also outlines the supporting and inhibiting factors in utilizing this incentive. The research approach used is qualitative with qualitative research methods. The data analysis technique used is qualitative data analysis technique. The types of data used are primary and secondary data through in-depth interviews and literature review. The research concludes that the evaluation of the PPh 21 DTP tax incentive policy in the trading sector in DKI Jakarta has not met Dunn's policy evaluation criteria. This research result indicates that the policy is not fair, responsive, and accurate enough, thus not aligning with the goal of increasing community purchasing power. In order to encourage the optimization of incentives, the government should emphasize the benefits from the perspective of businesses as parties carrying out administrative obligations in utilizing the PPh 21 DTP incentive.